AUTOMATIC DEFINITION THE FIELD OF VIEW OF CAMERA OF UNMANNED AERIAL VEHICLE - Buryi, P. (Science-based technologies, 2016)
In the last time more and more people use light unmanned aerial vehicles for solving tasks of research a territory. The main criterion is the task of exact linking received data to the location data. In the article offered the method of determining the coordinates of the field of vision of camera, which was based on the determine communication between the coordinates of corresponding points of area and snapshot. The aim is to develop an algorithm of determining the coordinates of the field of vision of camera and to carry out its testing on data of aerial photography. In the paper used the methods of geometry, projective geometry, computer graphics and digital imaging, military topography, that used to work with a digital camera and a digital snapshot. Designed the method and algorithm based on it for the automated determining the coordinates of the field of vision of camera. It was tested on real data. The results can be used to further development of software for tracking objects with drones, the preparation photomap, cards of heights and for stereo unmanned aerial vehicle orientation in space without using of global navigation systems.